Análise do sistema Fe2O3 - SnO2 sinterizado: propriedade de transporte eletrônico - Souza, Josiane Carneiro (2019)
Hematite (α-Fe2O3) is a very abundant chemical compound in nature, has interesting electrical and magnetic properties, which consequently makes this oxide an advanced functional material. The literature reports that Sn ions segregate in the grains boundaries of hematite, which reduces the potential barrier in this region, facilitating the electronic transport and, consequently, the increased conductivity of this material. This paper proposed a challenge with regard the preparation, the conventional sintering, and the structural, microstructural and electrical properties of this material without and with different nominal additions (1, 2, 5, 6 and 8 % wt.) of SnO2, in order to obtain smaller grain size and larger number of grains boundaries to study the behavior of Sn ions this solid-solid interface. The results obtained in the preparation of the starting materials, Fe2O3 and SnO2, allowed to control the obtaining of nanoparticles with morphology and medium size distribution appropriate to the use of the sintering process that contributed to the segregation of Sn ions in hematite ceramic matrix. The sintered samples showed a gradual decrease in resistance with increasing SnO2 addition. The sintered hematite sample without SnO2 addition did not show significant differences in capacitance results at both low and high frequencies, corresponding to the behavior of grains boundaries and hematite grain, respectively. Compared to the sintered samples, the nominal increase of 2%, 6% and 8% wt. of SnO2 showed an increase of capacitance by 1, 3 and 4 orders of magnitude, respectively, while the gradual increase of SnO2 in the samples of hematite favored the decrease of resistance. These results showed that the current flows through the hematite grain boundary region, the region with the highest conductivity, resulting from the segregation of Sn ions. In combination with the condutive atomic force microscope analysis, it has been shown that it is possible to identify the types of grains boundaries that most influence the electronic transport. The results allowed us to conclude a better understanding of the segregation of Sn ions grains boundaries in the ceramic matrix of hematite.